(untitled) (Research, Society and Development, 2022)
Introduction: The knowledge about the biology of obesity and apoptosis induction of adipose-derived stem cells (ADSCs) may support in the development of new therapies. Objective: The present research aimed to investigate the toxicogenic effect of all-trans retinoic acid (ATRA) as well as its influence in the adipogenic differentiation and expression of genes related to DNA damage, cell cycle and thermogenesis. Methodology: Cell cultures of human adipose-derived stem cells were treated for 12 hours with ATRA (20.75 μM) and were performed the adipogenic differentiation, comet assay, micronucleous, cell death, cell cycle and qPCR. Results: The ATRA treatment decreased the capacity of adipogenic differentiation of ADSCs. The comet assay demonstrated increase in nucleoid frequency with genomic damage and scoring. However, these damages were not fixed at the chromosome level, since the tail moment was not significant. The treatment with ATRA increased cytotoxicity and increased cell death by apoptosis. The relative expression of CHEK-1, CHEK-2, CDC25A, CDC25C, ATM and ATR decreased and only UCP1 increased significantly. Conclusion: The results of the present study demonstrate that the use of ATRA induces genomic damage in ADSCs, although it was eliminated in the apoptosis process. Therefore, administration of ATRA in ADSCs did not cause chromosomal instability, which suggests toxicogenic safety. Also it was considered that ATRA might active the browning effect. Thus, this compound is considered a promising candidate for the development of novel therapies for the treatment of obesity and / or localized fat by the use of mesotherapy.